Effect of Supplier–Buyer Collaboration, Product Innovation, Process Innovation, and Quality Management Adoption on Firm Performance - Ronaldo Richard Gunawan; Hotlan Siagian; Zeplin Jiwa Husada Tarigan (Master of Management, School of Business and Management, Petra Christian University, 2025)
Cooperation between companies, such as manufacturers and suppliers, can stabilize raw material procurement, ensuring the production process meets customer needs. Companies need to adopt quality management to innovate processes and products and achieve good performance. This study aims to examine the influence of supplier-buyer collaboration on firm performance through product innovation, process innovation, and Quality Management Adoption. Distribution of questionnaires to 103 manufacturing companies in East Java using purposive sampling techniques. The results of data processing using PLS version 4 software found that supplier-buyer collaboration has a direct influence on quality management adoption and innovation processes, but not on product innovation. The quality management adoption that is formed has a direct impact on the innovation process, product innovation, and firm performance. Companies that innovate processes can also innovate products, thereby further improving company performance. Periodic product innovation can enhance a firm's performance. The practical contribution of this research provides top management with insight to commit to building sustainable collaboration with suppliers to support innovation processes and quality management systems. It is recommended that companies adopt the ISO system to implement a standard quality system as needed. Terrorist contributions can strengthen the integration of quality management and supply chain management within the framework of a resource-based view.